Xingamento ou preconceito? Um estudo sobre o preconceito racial no futebol brasileiro - Ferreira, Andreza Silene Silva (2016)
This study aimed to examine to what extent racial prejudice in soccer mediates the relationship between the use of verbal abuse and compliance with legal actions that deny the existence of racial prejudice in soccer. In addition, we attempted to analyze the speeches that people use to position themselves in front of racial prejudice situations in soccer and what principles that organize this position paper. To achieve these objectives was carried out an exploratory and correlational study. The study gathered 295 students from a public university in the state of Paraiba, aged 15 and 61 years (M = 21, SD = 6.01) and 109 male and 185 female; one participant did not answer the question. The results showed that the relationship between the verbal and the agreement with the position of the judge to remove the racial slur charge was fully mediated by prejudice. The results also showed that the speech of the participants, in general, recognize the existence of the prejudice, but at the same time, refuse to gravity biased acts in the context of the soccer. Taken together, these results indicate that the manifestation of racial prejudice in brazilian soccer occur in the flagrant form, even if we consider a racial democracy. The highlighted speeches indicate that the positions of participants vary according to the anchors used for such placements, is the context of the dispute, in which some name calling stem from an unethical stance or are media constructions, either in the social context in which the name calling arise a biased stance and reflect brazilian society.